2006
DOI: 10.1007/s11664-006-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Polarization, piezoelectric constants, and elastic constants of ZnO, MgO, and CdO

Abstract: We report first-principles density functional calculations of the polarizations, piezoelectric stress constants, and elastic constants for the II-VI oxides MgO, ZnO, and CdO in the wurtzite structure. Using our pseudopotential selfinteraction corrected implementation of density functional theory, we obtain polarization values of ÿ0.060, ÿ0.022, and ÿ0.10 C/m 2 , and piezoelectric constants, e 33 (e 31 ) of 1.64 (ÿ0.58), 1.34 (ÿ0.57), and 1.67 (ÿ0.48) C/m 2 for structurally relaxed MgO (with its in-plane lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 27 publications
7
75
2
Order By: Relevance
“…An earlier DFT study has reported an extremely distorted hexagonal structure (c/a = 1.20, u = 0.5) for the wurtzite MgO, in which Mg sits on a mirror plane and has a bi-pyramidal coordination. 46 However recent studies, independently conducted by Janotti et al 47 and Gopal and Spaldin, 48 have reported c/a = 1.51 and u = 0.398. More relevant to our experimental work, Malashevich and Vanderbilt performed the geometry optimization of Zn 1−x Mg x O supercells (x = 0, 49 They showed that the c/a decreases with increase of Mg content, and u(Mg) is larger than u(Zn) in all the supercell compositions.…”
Section: 44mentioning
confidence: 96%
“…An earlier DFT study has reported an extremely distorted hexagonal structure (c/a = 1.20, u = 0.5) for the wurtzite MgO, in which Mg sits on a mirror plane and has a bi-pyramidal coordination. 46 However recent studies, independently conducted by Janotti et al 47 and Gopal and Spaldin, 48 have reported c/a = 1.51 and u = 0.398. More relevant to our experimental work, Malashevich and Vanderbilt performed the geometry optimization of Zn 1−x Mg x O supercells (x = 0, 49 They showed that the c/a decreases with increase of Mg content, and u(Mg) is larger than u(Zn) in all the supercell compositions.…”
Section: 44mentioning
confidence: 96%
“…The Bismuth doped ZnO sol of concentration 0.7 M have been prepared using precursor zinc acetate dehydrate (Zn(CH 3 COO) 2 .2H 2 O), isopropanol (solvent) and stabilizing agent diethanolamine (DEA). The molar proportion of zinc acetate dehydrates and stabilizer DEA was kept at 1:1.…”
Section: Deposition Of Bismuth Doped Zno Thin Filmmentioning
confidence: 99%
“…As far as the future of the semiconductor devices is concerned, ZnO has a major role to play in it as it is versatile and has interesting properties like resistivity control over the range of 10 −3 -10 -5 Ω-cm, transparency in the visible range, high electrochemical stability, direct band gap (3.3 eV), absence of toxicity and abundance in nature [1][2]. Therefore, it can be stated that versatility of ZnO ranges from optical, electrical, piezoelectricity, ferromagnetic to gas sensing properties [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, wurtzite ZnO has been extensively studied by virtue of its high piezoelectric tensor. [16][17][18][19][20] Moreover, ZnO nanostructures show a variety of different morphological configurations that include nanowires, 21 nanobelts, 22 nanosprings, 23 nanorings, 24 nanobows, 25 and nanohelices. 26 Among these nanostructures, nanowires exhibit remarkably enhanced piezoelectric responses.…”
Section: Introductionmentioning
confidence: 99%